Coin-operated Americans : rebooting boyhood at the video game arcade - Kocurek, Carly A. (University of Minnesota Press, 2015)
"Video gaming: it's a boy's world, right? That's what the industry wants us to think. Why and how we came to comply are what Carly A. Kocurek investigates in this provocative consideration of how an industry's craving for respectability hooked up with cultural narratives about technology, masculinity, and youth at the video arcade. From the dawn of the golden age of video games with the launch of Atari's Pong in 1972, through the industry-wide crash of 1983, to the recent nostalgia-bathed revival of the arcade, Coin-Operated Americans explores the development and implications of the "video gamer" as a cultural identity. This cultural-historical journey takes us to the Twin Galaxies arcade in Ottumwa, Iowa, for a close look at the origins of competitive gaming. It immerses us in video gaming's first moral panic, generated by Exidy's Death Race (1976), an unlicensed adaptation of the film Death Race 2000. And it ventures into the realm of video game films such as Tron and WarGames, in which gamers become brilliant, boyish heroes. Whether conducting a phenomenological tour of a classic arcade or evaluating attempts, then and now, to regulate or eradicate arcades and coin-op video games, Kocurek does more than document the rise and fall of a now-booming industry. Drawing on newspapers, interviews, oral history, films, and television, she examines the factors and incidents that contributed to the widespread view of video gaming as an enclave for young men and boys. A case study of this once emergent and now revived medium became the presumed enclave of boys and young men, Coin-Operated Americans is history that holds valuable lessons for contemporary culture as we struggle to address pervasive sexism in the domain of video games--and in the digital working world beyond."--